A participatory approach for comparing stakeholders' evaluation of P loss mitigation options in a high ecological status river catchment. Issue 84 (June 2018) - Micha, Evgenia; Roberts, William; Ryan, Mary; O'Donoghue, Cathal; Daly, Karen
Highlights: Successful implementation of water quality policies is uncertain due to conflicting stakeholders' interests. Experts' and farmers' perceptions are based on group-specific factors at different spatial and operational scales. Greater interaction between research and farming communities is needed for improved knowledge transfer. Decision support systems need to be calibrated to local conditions. Abstract: Phosphorus (P) transfer from land to water is a source of diffuse pollution that contributes to the decline in ecological status of river bodies in the European Union. The Water Framework Directive (2000/60/EC) provides for the protection of water bodies that represent pristine or near-pristine condition, classified as high ecological status through the adoption of an agri-environmental decision making process that promotes stakeholder participation. However, successful implementation of agri-environmental policies can prove challenging when faced with uncertainties and diverging opinions due to the variety of actors involved. This study adopted a participatory approach including stakeholders with conflicting interests in the selection of P transfer mitigation policies. Fifteen P transfer mitigation options were shortlisted based on agronomic and environmental data from a case-study agricultural catchment and presented to a group of experts and farmers. Results showed significant disparities between perceived effectiveness by farmers and experts groups, with experts prioritizing problems related to connectivity issues, while farmers to soil compaction and erosion. In addition, measured agronomic and environmental variables were used to model effectiveness from a decision support tool (FARMSCOPER) and compared with stakeholder groups' perceived effectiveness. This approach combined the scientific research with the empirical knowledge of farmers and the modelling of quantified field and farm data. This study showed that stakeholders are diverse, and perceive effectiveness based on group-specific operational and social factors. Experts identified effectiveness at catchment scale, whilst farmers identified field scale effectiveness. For decision support tools and simulation models to be beneficial for policy makers, they need to be calibrated to local conditions and farm typologies to select the right measure at farm scale. The study recommends improved knowledge transfer between interested actors and the need for integration of conflicting opinions in policy design. A bottom-up approach to decision making is suggested, to assist in the decentralization of the procedures towards more effectively implemented P transfer mitigation policies.